2022
DOI: 10.3390/nu14194082
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K-Dependent Carboxylation of Osteocalcin in Bone—Ally or Adversary of Bone Mineral Status in Rats with Experimental Chronic Kidney Disease?

Abstract: Chronic kidney disease (CKD) commonly occurs with vitamin K (VK) deficiency and impaired bone mineralization. However, there are no data explaining the metabolism of endogenous VK and its role in bone mineralization in CKD. In this study, we measured serum levels of phylloquinone (VK1), menaquinone 4 and 7 (MK4, MK7), and VK-dependent proteins: osteocalcin, undercarboxylated osteocalcin (Glu-OC), and undercarboxylated matrix Gla protein (ucMGP). The carboxylated osteocalcin (Gla-OC), Glu-OC, and the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Bacteroides is the main synthetic bacteria for vitamin K. In vivo , vitamin K is mainly involved in blood coagulation. The carboxylase system dependent on vitamin K not only plays an important role in blood coagulation but is also related to the formation of the calcium binding protein osteocalcin [ 64 , 65 ]. Bacteroides can prevent or treat osteoporosis by increasing bone density [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides is the main synthetic bacteria for vitamin K. In vivo , vitamin K is mainly involved in blood coagulation. The carboxylase system dependent on vitamin K not only plays an important role in blood coagulation but is also related to the formation of the calcium binding protein osteocalcin [ 64 , 65 ]. Bacteroides can prevent or treat osteoporosis by increasing bone density [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The undercarboxylated OC (ucOC) is an inactive form, while the active carboxylated form of OC has an increased affinity with free calcium ions and hydroxyapatite (HA), which subsequently inhibits the abnormal HA crystallization formation and cartilage mineralization speed and maintains the normal mineralization rate [61]. A previous study has shown that serum levels of ucOC may be more sensitive to VK status and can thus be used to detect subclinical VK deficiency [62]. Double-blind, randomized controlled trials reported that supplementation with ≥100 µg MK-7 in diets could improve OC γ-carboxylation status [63].…”
Section: Vitamin K-dependent Proteinsmentioning
confidence: 99%